PENGUASAAN KOSAKATA MELALUI MEDIA TEKA-TEKI SILANG PADA SISWA KELAS III SEKOLAH DASAR - H. IBRAHIM, NATALIYA; HUSAIN, RUSMIN; HALIDU, SALMA; T. PULUKADANG, WIWY; KATILI, SUKRI (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
The research problem in this study is: "Can crossword puzzle media improve the vocabulary mastery of third-grade students at SDN 2 Talaga Jaya?" This study aims to enhance the vocabulary mastery of third-grade students at SDN 2 Talaga Jaya through the use of crossword puzzle media. The research method applied is Classroom Action Research (CAR), with data collection techniques including tests, observations, and documentation. The research subjects consist of 19 third-grade students.During the initial observation, 16 out of 19 students (84%) still had low vocabulary mastery. The improvement was demonstrated through the implementation of classroom action research, conducted over two cycles, each consisting of two meetings. In the first meeting of Cycle I, 4 students (21%) showed improvement in vocabulary mastery. In the second meeting of Cycle I, 8 students (42%) exhibited increased vocabulary mastery. In the first meeting of Cycle II, the number of students showing improvement increased to 14 (73%). By the second meeting of Cycle II, vocabulary mastery had further improved, reaching 89%, with 17 students successfully enhancing their vocabulary skills.The research findings reveal that the use of crossword puzzle media significantly contributes to improving the vocabulary mastery of third-grade students at SDN 2 Talaga Jaya. ABSTRAK Rumusan masalah dalam penelitian ini yaitu “Apakah media teka-teki silang dapat meningkatkan penguasaan kosakata siswa kelas III di SDN 2 Talaga Jaya?”. Penelitian ini bertujuan untuk meningkatkan penguasaan kosakata siswa kelas III SDN 2 Talaga Jaya melalui penggunaan media teka-teki silang. Metode yang diterapkan dalam penelitian ini adalah Penelitian Tindakan Kelas (PTK), dengan teknik pengumpulan data yang mencakup tes, observasi, dan dokumentasi. Subjek penelitian terdiri dari 19 siswa kelas III. Pada observasi awal dari 19 siswa, 16 siswa (84%) masing kurang dalam penguasaan kosakata. Peningkatan tersebut dibuktikan dengan hasil pelaksanaan tindakan kelas siklus I sebanyak dua kali pertemuan dan siklus II dua kali pertemuan. Pertemuan pertama pada siklus I capaian 19 siswa penguasaan kosakata memperoleh (21%) atau 4 orang siswa yang meningkat. Siklus I pertemuan II penguasaan kosakata siswa memperoleh (42%) atau 8 orang siswa meningkat. Siklus II pertemuan I penguasaan kosakata siswa meningkat menjadi 14 orang (73%) dalam penguasaan kosakata. Pada siklus II pertemuan II mengalami peningkatan penguasaan kosakata menjadi (89%) atau 17 siswa sudah mampu dalam penguasaan kosakata. Hasil penelitian mengungkapkan bahwa pemanfaatan media teka-teki silang secara signifikan berkontribusi dalam meningkatkan penguasaan kosakata siswa kelas III SDN 2 Talaga Jaya.